Revised transport estimates of the Denmark Strait overflow. Issue 4 (28th April 2017) - Jochumsen, Kerstin; Moritz, Martin; Nunes, Nuno; Quadfasel, Detlef; Larsen, Karin M. H.; Hansen, Bogi; Valdimarsson, Hedinn; Jonsson, Steingrimur
Abstract: The major export route of dense water from the Nordic Seas into the North Atlantic is in the deep channel in Denmark Strait. Here currents have been monitored with one or two moored Acoustic Doppler Current Profilers (ADCPs) since 1996. Volume transport estimates of the Denmark Strait Overflow Water (DSOW) so far were based on these data, which were regressed to the total transport of dense water in a numerical model. The resulting transport has been used in many publications. Here we present results from an extended five‐mooring array deployed in 2014/2015, which included measurements outside the swift overflow core. This array provided the basis for new calculations to estimate the DSOW transports. Furthermore, a correction is proposed for biases detected on some ADCPs, which led to earlier underestimation of the flow in the lower part of the plume. Using the new method, the mean DSOW transport is estimated to be 3.2 Sv in the period 1996–2016, without a significant trend. Uncertainties are typically ±0.5 Sv. Beyond variations on the eddy scale, an empirical orthogonal functions (EOF) analysis of the velocity field reveals three dominant modes of variability: the first mode is roughly barotropic and corresponds to pulsations of the plume, the second mode represents the laterally shifting component of the plume's core position, and the third mode indicates the impact of the varying overflow thickness. Finally, DSOW transports are compared to the Faroe Bank Channel overflow transports, but no clear relationship is found. Key Points: A new calculation method for the DSO based on observations is introduced, which provides estimates from 1996 to 2016 Velocity measurements from near‐bottom moorings using ADCPs of the Workhorse Longranger type (75 kHz) show a low‐velocity bias Overflow variability beyond the eddy scale can be explained to 90% by three modes. No long‐term trend was found